One-pot catalytic conversion of sucrose to 1,2-propanediol over titania supported Ni-Ce metal catalyst under milder reaction conditions - Sreekantan, Sreejith; Sreedharan, Sarath; Kirali, Arun Arunima Balachandran; Yadav, Parmeshwar; Marimuthu, Banu (Biomass Conversion and Biorefinery, 2024)
The increased energy demand and decreasing fossil resources have driven the research community to look into a sustainable, green process to meet the energy demands. India being one of the top producers of sugarcane derived sucrose, and conversion of surplus sucrose to value chemicals is always an advantage. 5%Ni-15%Ce/TiO2 catalyst is found to produce high yield of 1,2-PDO (similar to 74%) under very mild reaction condition of 180 degrees C, 30 bar H-2 for 3-h reaction time. The characterization of the catalyst by using various physicochemical methods indicates the synergy between Ni-Ce bimetal which enhances the selective production of glycol. The low temperature and pressure requirement and the advantage of being the one-pot process will always attract the future scope of commercialization.
Keywords: Glycol; Low pressure; Low temperature; Ni-Ce catalyst; Sucrose; titania